Study on the Ecological Circulation Agricultural System of Combining Planting and Raising of Berry Tea - Cao, Defang; Zhang, Xiuju; Mo, Shengyuan; Luo, Guihua; Qin, Zhengfang; Qin, Hanfeng (Research on World Agricultural Economy, 2021)
Berry tea is a perennial vine. Its scientific name is ampelopsis grossedentata. It belongs to vitaceae and is widely spread in the Tujia people of Xiangxi, Hunan Province. By adopting appropriate agricultural planting technology, rational use of organic selenium fertilizer and nutritional conditioner, we can produce high-quality berry tea with more healthy and even medicinal value and high selenium content, and realize double protection of human health with high selenium content and high flavonoids. Under the existing planting system, through the supplement of breeding links, constructing ecological recycling agricultural system combining planting and raising, not only can greatly enrich the supply of table agricultural products, but also can effectively ensure the high quality and high safety of agricultural products, and can effectively enrich the local agricultural industrial structure. ER